Evaluasi Efektivitas Sosialisasi JKN-KIS dalam Meningkatkan Akses Layanan Kesehatan bagi Masyarakat Negeri Liang - Matulessy, Febby Sonya; Salakory, Hans Sammy Marthin; Papalia, Yunita; Marasabessy, Rio Irawan (Universitas Nusantara PGRI Kediri, 2025)
This Community Service (PKM) activity aims to increase the understanding and awareness of the Liang Village community regarding the National Health Insurance - Healthy Indonesia Card (JKN-KIS), as well as to facilitate health cadres in disseminating information about the program. The socialization was held on December 28, 2024, at the Liang Village Hall, with the main participants being local health cadres. This activity included lecture sessions, interactive discussions, and a simulation of using the Mobile JKN application to facilitate the community in accessing health services through a digital platform. The material presented included an introduction to JKN-KIS, registration procedures, how to use the JKN-KIS card, and the health service claim mechanism. The method used in this socialization was a participatory approach, involving questions and answers and discussions to ensure participant understanding. The expected results of this activity are increased knowledge of health cadres about JKN-KIS, as well as increased public awareness of the program's importance in improving access to health services. In addition, this activity also aims to empower health cadres so that they can effectively disseminate this information to the community in their environment. Thus, this activity is expected to support the government's efforts to expand the coverage of JKN-KIS participants and improve the quality of health services in the community.